Evaluation of the guide holder in acute myocardial infarction with ST-segment elevation in a hospital in the city of Caxias do Sul (Research, Society and Development, 2022)
AMI is defined as myocardial cell death, causing necrosis of the heart muscle in an acute way, the diagnosis can be given in several ways. It is recommended to perform emergency coronary reperfusion in the first hours after having the diagnosis of STEMI, as it has a significant impact on patient survival. Thus, the general objective of this study was to evaluate the time that the patient takes from his arrival to the treatment of his coronary artery, through the guide-holder indicator. The study is cross-sectional, descriptive, observational and retrospective, which was carried out at Hospital Geral de Caxias do Sul. The door-to-balloon time is an indicator of quality in the care of patients with STEMI in institutions that have a hemodynamics sector, as it is related to prognosis and mortality, being essential to reduce the morbidity and mortality of the disease. According to the evaluation of the data of the indicators, it was often associated with the clinical condition of the patient requiring hemodynamic stability, as well as starting with vasopressor drugs, so care must occur between 90 min of the door-to-balloon time, as recommended by cardiology guidelines, because is associated with survival and other relevant outcomes that can be observed, including the evolution of the treatment of patients, both in the short and long term. But even so, this protocol or institutional indicator should always be valued as it involves and reflects in the results of joint actions, in the various critical points of AMI care, it involves the recognition of symptoms, structure, multidisciplinary team, all involved in a single purpose, the most effective treatment. of the patient, thus guaranteeing an assistance with quality and efficiency.